Patterns of Incorporation of Latinos in Old and New Destinations: From Invisible to Hypervisible. (December 2014) - Vaquera, Elizabeth; Aranda, Elizabeth; Gonzales, Roberto G.
This special issue introduces a range of articles that analyze patterns of incorporation among Latinos living in the United States. We discuss the importance of race and institutionalized discrimination across various social institutions and through legislation and policies that promote and/or blunt Latino incorporation. Building on the findings of the studies in this special issue, this introduction considers how race and racialization shape the lives of Latino youth and adults through directives and policies emerging from a range of institutions—from the U.S. Census Bureau to State Courts, and state and federal legislative bodies. Mediating incorporation is legislation such as the Affordable Care Act and administrative changes such as the Deferred Action for Childhood Arrivals program, which, while promoting inclusion of Latino populations into the U.S. body-politic, also render some Latinos part of a class of people that are subjugated based on their origins. We conclude this introductory article with an assessment of how this structural discrimination results in various forms of incorporation that include marginalized belonging, blocked mobility, and both the invisibility and hypervisibility of Latinos in the United States.